2017
DOI: 10.1261/rna.060335.116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the mammalian DEAD-box protein DDX5 reveals functional conservation with S. cerevisiae ortholog Dbp2 in transcriptional control and glucose metabolism

Abstract: DEAD-box proteins are a class of nonprocessive RNA helicases that dynamically modulate the structure of RNA and ribonucleoprotein complexes (RNPs). However, the precise roles of individual members are not well understood. Work from our laboratory revealed that the DEAD-box protein Dbp2 in is an active RNA helicase in vitro that functions in transcription by promoting mRNP assembly, repressing cryptic transcription initiation, and regulating long noncoding RNA activity. Interestingly, Dbp2 is also linked to glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 80 publications
(128 reference statements)
3
59
1
Order By: Relevance
“…A further notable difference between DDX3X and Ded1p is the absence of pronounced strand annealing activity by DDX3X. This observation parallels a recent report for the DEAD-box helicase orthologs Dbp2p from S.cerevisae and DDX5X from human, where the yeast ortholog also shows stronger strand annealing activity than the human protein (47). …”
Section: Discussionsupporting
confidence: 84%
“…A further notable difference between DDX3X and Ded1p is the absence of pronounced strand annealing activity by DDX3X. This observation parallels a recent report for the DEAD-box helicase orthologs Dbp2p from S.cerevisae and DDX5X from human, where the yeast ortholog also shows stronger strand annealing activity than the human protein (47). …”
Section: Discussionsupporting
confidence: 84%
“…Previous results from our laboratory showed that the ortholog of DDX5 in S. cerevisiae, Dbp2 (Xing et al 2019), is required for efficient termination of RNAPII transcription, as loss of DBP2 results in accumulation of a 39 extended GAL10 mRNA and GAL10s long, noncoding RNA (Cloutier et al 2012). Both Dbp2 and DDX5 exhibit highly efficient RNA duplex unwinding in vitro, consistent with a role in altering secondary structure Xing et al 2017). Furthermore, Dbp2 associates with actively transcribed chromatin in an RNA-dependent manner and is required for pre-mRNA maturation and messenger RNP assembly, as evidenced by reduced binding of export factors Nab2, Yra1, and Mex67 in dbp2D cells .…”
supporting
confidence: 53%
“…DDX5 resolves R-loops in vitro and in vivo DDX5 is an RGG/RG motif-containing helicase previously shown to unwind RNA:RNA and RNA:DNA duplexes (Hirling et al, 1989;Rossler et al, 2001;Xing et al, 2017). Dbp2, the S. cerevisiae homolog of DDX5, was shown to resolve RNA:DNA hybrids in the context of R-loops (Cloutier et al, 2016); however, whether DDX5 shares this R-loop resolving activity is unknown.…”
Section: Resultsmentioning
confidence: 99%